On the Difference between Self-Assembling Process of Monomeric and Dimeric Surfactants with the Same Head to Tail Ratio: A Lattice Monte Carlo Simulation - Reza Behjatmanesh-Ardakani; Maryam Farsad (Journal of Chemistry)
Experimental data show that gemini surfactants have critical micelle concentrations that are almost tenfold lower than the CMCs of single chain ones. It is believed that the spacer groups play an important role in this subject. Short hydrophilic or long hydrophobic spacers can reduce CMC dramatically. In this paper, self-assembling processes of double-chain and one-chain surfactants with the same head to tail ratio are compared. Dimeric chain structure is exactly double of single chain. In other words, hydrophilic-lyophilic balances of two chain models are the same. Two single chains are connected head-to-head to form a dimeric chain, without introducing extra head or tail beads as a spacer group. Premicellar, micellar, and shape/phase transition ranges of both models are investigated. To do this, lattice Monte Carlo simulation in canonical ensemble has been used. Results show that without introducing extra beads as spacer group, the CMC of (H3T3)2 as a dimeric surfactant is much lower than the CMC of its similar single chain, H3T3. For dimeric case of study, it is shown that bolaform aggregates are formed.